Native strains of the marine bacterioneuston and inhibitory activity of ichthyopathogenic bacteria - León, Jorge (1998)
Marine bacteria have been frequently included in the scientific literature as producers substance antibacterial properties. In this study, we investigate the potential activity antibiotic in vitro of strains the marine bacterioneuston isolated from rocky litoral pools in Montemar Beach, Bay of Valparaiso, Chile. Were isolated 71 strains antagonic to Staphylococcus aureus ATCC 11632. Twentyfive strains producing strongly inhibitory substance were tested against 15 know ichthiopathogenic bacteria. Applying a classic method for marine bacteria, they were carried out phenotypic characterization of bacterioneuston strains accordingly to identified. Results showed that all fifteen ichthiopathogens strains were inhibeted by the neustonic isolates, being V anguillarum NCMB 2133, V ordalii 84/2559 and V tubiashii EX1 the most sensitive. Strains of bacterioneuston were identified as Vibrio spp. (28%), Flavobacterium spp. (12%), AlteromonasMarinomonas group (12%), Pseudomonas spp. (8%) and Micrococcus spp. (4%). Nine neustonic isolates did not match our identifications schemes. Experimental results suggest that this strains or their products coullo be useful in activities of intensive cultivation of aquaculture fish, mollusks and crustaceans.